2018
DOI: 10.1186/s12933-018-0741-9
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of sodium–glucose linked cotransporters 1 and 2 exacerbates cardiac dysfunction following experimental myocardial infarction

Abstract: BackgroundInhibiting both type 1 and 2 sodium–glucose linked cotransporter (SGLT1/2) offers the potential to not only increase glucosuria beyond that seen with selective SGLT2 inhibition alone but to reduce glucose absorption from the gut and to thereby also stimulate glucagon-like peptide 1 secretion. However, beyond the kidney and gut, SGLT1 is expressed in a range of other organs particularly the heart where it potentially assists GLUT-mediated glucose transport. Since cardiac myocytes become more reliant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…This aligns with our previous findings showing that cardiac SGLT1 is involved in an important protective mechanism against IRI by replenishing ATP stores in ischemic cardiac tissues via enhanced glucose utilization [7]. Consistent with a series of our studies, Connelly et al showed that oral administration of a dual SGLT1/2-inhibitor led to an impaired cardiac function after myocardial infarction in a rat model with left anterior descending coronary artery ligation, while a selective SGLT2-inhibitor had no significant effect on this condition [38]. These data indicate that cardiac SGLT1 exerts protective effects against myocardial ischemia even in vivo, although they used a non-diabetic model rather than HFD-induced diabetic Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This aligns with our previous findings showing that cardiac SGLT1 is involved in an important protective mechanism against IRI by replenishing ATP stores in ischemic cardiac tissues via enhanced glucose utilization [7]. Consistent with a series of our studies, Connelly et al showed that oral administration of a dual SGLT1/2-inhibitor led to an impaired cardiac function after myocardial infarction in a rat model with left anterior descending coronary artery ligation, while a selective SGLT2-inhibitor had no significant effect on this condition [38]. These data indicate that cardiac SGLT1 exerts protective effects against myocardial ischemia even in vivo, although they used a non-diabetic model rather than HFD-induced diabetic Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, we focused on the latter to assess cardiac function in rats with heart failure. Whilst cardiac function was impaired post MI, empagliflozin failed to improve load dependent measures such as fractional shortening consistent with previous reports from our group using dapagliflozin in the post MI setting [12]. In contrast, load independent measures of cardiac contractility were improved in empagliflozin treated animals post MI.…”
Section: Discussionsupporting
confidence: 88%
“…Diameter measurements were taken membrane to membrane across the narrowest point that crosses the nucleus. The average diameter of 30-50 myocytes per animal was measured, as previously described [12].…”
Section: Histopathologymentioning
confidence: 99%
“…A recent study reported that chronic cardiac overexpression of SGLT1 in mice led to pathological cardiac hypertrophy and left ventricular failure, and cardiac knockdown of SGLT1 attenuated the disease phenotype 107 . In contrast, a recent study also reported that dual SGLT1/SGLT2 inhibitor exacerbated cardiac dysfunction after experimental myocardial infarction in rats 108 . Considering that SGLT2 is not expressed in the heart, this effect might be linked to SGLT1 inhibition.…”
Section: Overview Of Sgltsmentioning
confidence: 99%